Postmetamorphic cell death in the nervous and muscular systems of Drosophila melanogaster - Kimura, KI (J Neurosci, 1990)
Programmed cell death occurs in the nervous and muscular system of newly emerged adult Drosophila melanogaster. Many of the abdominal muscles that were used for eclosion and wing-spreading behavior degenerate by 12 hr after eclosion. Related neurons in the ventral ganglion also die within the first 24 hr. Ligation experiments showed that the muscle breakdown is triggered by a signal from the anterior region, presumably the head, that occurs about 1 hr before adult emergence. The timing of this signal suggests that eclosion hormone may be involved. Although muscle death is triggered prior to ecdysis, it can be delayed, at least temporarily, by forcing the emerging flies to show a prolonged ecdysis behavior. In contrast to the muscles, the death of the neurons is triggered after emergence. The signal for neuronal degeneration is closely correlated with the initiation of wing inflation behavior. Ligation and digging experiments and behavioral manipulations that either blocked or delayed wing expansion behavior had a parallel effect in suppressing or delaying neuronal death.